ANALISIS GENDER DIVERSITY, CORPORATE GOVERNANCE DAN LEVERAGE DALAM MEMPREDIKSIKAN KONDISI FINANCIAL DISTRESS PADA FAMILY BUSINESS - Rodiah, Siti Ratu; Kristanti, Farida Titik (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.10.NO.11.TAHUN.2021DO - 10.24843/EEB.2021.v10.i11.p08, 2021)
Economic growth in the world is currently experiencing a very rapid increase, so companies must make strategies to be able to compete in facing challenges to survive. Financial distress is one of the factors that causes the company to be unable to achieve its goals so that the company cannot maintain its life. This study uses internal factors, namely gender diversity, institutional ownership, management ownership, and independent commissioners and external factors are leverage in family business. This research method is a quantitative method using time series data. The regression model used is a logistic regression model. Purposive sampling is the method used so that 80 samples were used in this study. Based on the partial test, institutional ownership, management ownership and independent commissioners have no significant effect on financial distress. Only gender diversity and leverage have a significant positive effect on financial distress.